Fundamental development and the design of an efficient cascade aerator - Din, Abdul Talib; Ali, Yusoff; Abdullah, Shahrir; Rahimi, Roslina Aida (2010)
Cascade aerators are normally used in water treatment for recreational lakes and fish raring ponds and also in the post aeration of drinking water supply, which generally have quite low efficiencies with dissolved oxygen serves as healthcare element in the human body when consumed as drinking water. The objective of this research is to develop and design an efficient cascade aerator for treated water based on the plunging water jet. The development of the cascade aerator in the past since the industrial revolution is studied and analyzed in order to identify the relationships between the properties of the cascade aerator with the important parameters such as water potential energy, water flow-rate, conditions of atmospheric air, diffusivity and dissolvability of air-water, saturation level of dissolved oxygen, water temperature and water pressure. The geometrical parameters involved are the height of plunging of water jet, angle of plunging water jet with respect to horizontal plane, size of water jet nozzle pipe, height of cascading, depth of water in lower tank and depth of water in upper tank. In the first stage, research is focused on identifying the parameters that influence the performance of a cascade aerator by means of theoretical study and by referring to the finding of the earlier research works. The relationship equation between height of cascading H and the ratio of dissolved oxygen deficit, R and also the other parameters consisting of temperature, T , water quality coefficient, a, geometrical parameters coefficient, b for a 4 stage weir based cascade aerator which had been developed by Barrett, relating height of cascading H which is proportional to the ratio of Oxygen deficit and inversely proportional to the temperature, is used as the basis for deriving the equations for the new design of cascade aerator based on the plunging water jet. While the general aeration equation in term of dissolved oxygen gradient proportional to the overall aeration coefficient value of the aerator, KLa is used as the basis to determine the coefficient of oxygen mass transfer of the whole cascade aerator. The following stage of research works is to determine the optimum points of test parameters in an empirical experiment by collecting data from a single stage, single nozzle model of cascade aerator based on the dissolved oxygen concentration values for several nozzle pipe’s internal diameter,  of 10 mm, 14 mm, 18mm, 20 mm. While the angle of plunging jet is varied by changing the angular position of the nozzle so as to produce angle of impact,  is tested at 30o, 45o, 60o, 75o and 90o. The water jet plunging height, H is tested at several vertical distances of 170 mm, 280 mm, 330 mm, 400 mm, and 500 mm. The depth of water in the lower tank, dt is tested at several depth of 145 mm, 175 mm, 200 mm, 245 mm and 280 mm. While the depth of water in the upper tank, da is tested at several depth of 410 mm, 450 mm, 510 mm, 580 mm and 700 mm. The results of the experiment found that the optimum height of plunging of the water jet, H is at 330 mm and the optimum angle of water jet,  and  with respect to the horizontal plane are 50o at inception point and 56o at impact point at the nozzle and at the lower tank water surface respectively. Optimum diameter of the plunging jet  is 19 mm while the optimum depth of lower water tank is 190 mm and finally the optimum depth of upper water in the upper tank is at 515 mm. The results obtained in experimental study is then validated by using computer simulation program, CFD (FLUENT) and test on the prototype based on the optimum parameters. The optimum geometrical parameters obtained and validated above are used as the basis of the new design of an efficient plunging water jet based cascade aerator for the post aeration process of treated water supply.